An Insight into Ocular Genetics - Shilpa Bisht; Manoj Kumar; Surabhi Gautam; Rima Dada (Delhi Journal of Ophthalmology)
Over the past decade, there has been an exponential increase in the database of heritable eye disorders. More than 100,000 germline mutations reported in more than 3,700 different human nuclear genes are associated with inherited diseases. Continuously increasing mutation database has revolutionized the study of human genome and facilitated “personalized genomics.” With more than 300 new “inherited disease genes” being identified annually, it is essential to ask how many inherited disease genes” are in the human genome, containing how many mutations, and where they are located? Knowledge of the clinical and molecular features of ocular genetics and inherited eye diseases is important for appropriate diagnosis and patient management. Genetic causes for a wide range of eye diseases have been identified, leading to discovery of genes associated with the eye disorder. Discovery of these new genes have led to a rethinking and a reclassification of eye disorders that were earlier based only on classical clinical signs, but now also on underlying genetic aetiology. Some of these disorders include the corneal dystrophies, rare forms of strabismus, ocular disorders resulting from mutations in transcription factors, cataract that result from mutations in crystallins and other structural lens components, retinal dystrophies that result from defects in phototransduction or visual cycle defects and many more. This article discusses molecular basis of some of these eye disorders and also advances in the field of ophthalmic genetics.